Moral uncertainty and public justification - Barrett, J; Schmidt, AT (Michigan Publishing, 2024)
Moral uncertainty and disagreement pervade our lives. Yet we still need to make decisions and act, both individually and politically. So, what should we do? Moral uncertainty theorists provide a theory of what individuals should do when they are uncertain about morality. Public reason liberals provide a theory of how societies should deal with reasonable disagreements about morality. They defend the public justification principle: state action is permissible only if it can be justified to all reasonable people. In this article, we bring these two approaches together. Specifically, we investigate whether considerations of moral uncertainty support public reason liberalism: given moral uncertainty, should we favor public justification? We argue that while moral uncertainty theory cannot vindicate an exceptionless public justification principle, it supports adopting public justification as a pro tanto principle – albeit one that can be overridden when the moral stakes are high. It also provides new answers to some intramural debates among public reason liberals and new responses to some common objections.